مدى توافر البُعدين الوطني والعالمي في منهاج الدراسات الاجتماعية للصفّ الرابع الأساسي في الجمهورية العربية السورية (دراسة تحليلية)
This study aimed to develop a list specifying the fields and issues of national and global dimensions in the social studies curriculum for fourth primary grade , analysis it according to them, and compare the proportion of the availability of the issues these two dimensions in this curriculum, and to monitor the views of teachers and supervisors in this row; about the availability of each dimension with their fields and issues. sample of study : first; Social Studies book for fourth grade primary the copy year (2014/2015) and the teacher’s guide for this book, which is titled Social Studies, Syrian Arab Republic,Second: a sample of teachers included (63) teachers, and (16 ) supervisor. The researcher used the descriptive and analytical content analysis, and a list of the most important fields and issues of national and global dimensions of their preparation and made the analysis on it ,and questionnaire targeted to teachers and supervisor, including fields and previous issues. and highlighted the findings of the study : the inclusion of the objectives and content of the Social Studies fourth grade primary on national and global dimensions of the six ranges, but the difference is clear and large in favor of the national dimension; where the percentage of targets (75,7%) and in content (73,9%), most of the teachers and supervisors agreed to exceed the national dimension, especially economic and political, and from the results also no difference statistically significant between percentage included dimensions between the objectives and content of the book. And proposals submitted by the researcher: enrich the curriculum with a number of relevant national values volunteer work; and social solidarity, and to promote dialogue and a culture of respect others opinions, and to listen and attention, include Social Studies basic fourth grade some of the global dimension of the subjects, commensurate with the level of education of the learner. هدفت هذه الدراسة إلى وضع قائمة تُحدد مجالات وقضايا البُعدين الوطني والعالمي في منهاج الدراسات الاجتماعية للصفّ الرابع الأساسي لتحليليه وفقاً لها, ومقارنة نسب توافر قضايا هذين البُعدين في هذا المنهاج، ورصد آراء معلّمي وموجهيّ هذا الصفّ في مدى تناول هذا المنهاج لكلٍّ من البُعدين بمجالاتهما وقضاياها. وتمثّلت عيّنة الدراسة، أولاً: كتاب الدراسات الاجتماعية للصفّ الرابع الأساسي للعام (2014/2015) ودليل المعلم لهذا الكتاب, والذي يحمل عنوان